Karakteristik Kimia Biskuit dari Tepung dan Serat Ubi Jalar Ungu - Stefani Limanto; Elisa Julianti; Zulkifli Lubis (Jurnal Teknologi dan Industri Pertanian Indonesia, 2019)
Purple sweet potato is one type of tuber that is rich in carbohydrates in the form of starch and fiber. It also contains purple anthocyanin pigments. In this research, purple sweet potato was processed into flour and starch. Starch processing solid waste can be utilized by processing it into fiber flour. Purple sweet potato flour and fiber were then used as the basis for making biscuits at a ratio of 75: 25 and compared to biscuits made from 100% purple sweet potato flour and wheat flour. The resulting biscuits were then analyzed for their chemical characteristics. The results showed that the ratio of flour gave a very significantly different effect on the value of water content, total dietary fiber content, insoluble dietary fiber content and % nutritional adequacy rate of food fiber, and had no significant effect on the value of ash content, protein content, fat content, content carbohydrates, total flavonoids, insoluble dietary fiber content, calorie intake and fulfillment of daily energy adequacy.